Liquid crystal based tunable spurline filters with notch frequencies at 50 and 85 GHz. Issue 3 (5th February 2018) - Economou, Evangelos C.; Lovejoy, James; Harward, Ian; Nobles, Jason E.; Kula, Przemyslaw; Herman, Jakub; Glushchenko, Anatoliy; Celinski, Zbigniew
Abstract: Electrically tunable double‐spurline notch filters with a nematic liquid crystal (LC) material as a dielectric medium were modeled, manufactured, and characterized. The spurlines, which were embedded into an inverted microstrip, consisted of quarter‐wavelength resonant elements. A Finite Difference Time Domain solver was used to model the filters. Photolithography and thin film deposition were employed to create the filters, followed by standard LC cell assembly. The filters, with central notch frequencies at 50 and 85 GHz, were characterized on‐wafer with a vector network analyzer. The stopband frequencies were tunable by 3% when a 14 volt peak‐to‐peak AC bias was applied across the 38 μm thick LC layer (electric field of 0.19 V/μm). The minimum stopband insertion loss of both filters achieved lower than −50 dB, while the stopband return loss varied from −4 to −12 dB. The −3 dB passband widths of the stopband filters were 12.2 and 28.3 GHz for the 50 and 85 GHz filters, respectively, giving a Q‐factor of 3–4.